2019
DOI: 10.1016/j.cmi.2018.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Are we missing respiratory viral infections in infants and children? Comparison of a hospital-based quality management system with standard of care

Abstract: Disease-burden estimates and surveillance should account for the underreporting of cases in routine care. Future studies should explore the effect of ILI screening and surveillance in various age groups and settings. Diagnostic algorithms should be based on the WHO ILI case definition combined with targeted testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…Epidemiological understanding of seasonal coronaviruses (sCoVs) is currently incomplete in many settings around the world, primarily due to the fact that these viruses are not a part of standard diagnostic armamentarium, or testing is guided by specific clinical case definitions (6). It is well-established that sCoVs are endemically found in co-circulation with other prevalent respiratory viruses, which is a principal reason why co-infections are commonly observed (7)(8)(9).…”
Section: Seasonal Coronavirusesmentioning
confidence: 99%
“…Epidemiological understanding of seasonal coronaviruses (sCoVs) is currently incomplete in many settings around the world, primarily due to the fact that these viruses are not a part of standard diagnostic armamentarium, or testing is guided by specific clinical case definitions (6). It is well-established that sCoVs are endemically found in co-circulation with other prevalent respiratory viruses, which is a principal reason why co-infections are commonly observed (7)(8)(9).…”
Section: Seasonal Coronavirusesmentioning
confidence: 99%
“…The concept of measuring individual-level differences in disease severity has drawn the attention of both public health stakeholders and regulatory agencies in recent years (18)(19)(20). The impact of RSV infections of course should be differentiated from the disease caused by influenza and other viral respiratory infections (21,22). However, a recent extensive literature review and prospective cohort have shown that in infants and children this cannot be done based on clinical symptoms alone; distinguishing RSV from other viral respiratory infections requires laboratory confirmation (23,24).…”
Section: Epidemiology Of Rsv Infectionmentioning
confidence: 99%
“…RSV is a single-stranded RNA virus (Figs. 1 and 2), which represents the most frequent viral cause of acute lower respiratory tract infection (ALRTI) in infants, with a worldwide distribution and seasonal occurrence (2)(3)(4)(5). It was first isolated in 1956 from nasal secretions of chimpanzees with rhinorrhea and coryza; the novel virus was…”
Section: Introductionmentioning
confidence: 99%
“…In a quality improvement (QI) programme in Berlin in collaboration with the National Reference Centre for Influenza at the Robert Koch institute, we established a QI team (independent from routine care) that would assess all influenza-like illness (ILI) patients taking samples to be tested for respiratory viruses. We learned that without the QI system in place, we would have missed the majority of specific respiratory viral diagnoses (5). Among 6,073 individuals with ILI qualifying for the QI programme, only 8.7% (528/6,073) would have undergone virus diagnostics during routine care.…”
Section: Questions and Answersmentioning
confidence: 99%
“…Emergency room surveillance based on ICD codes would have missed 61% (359/587) of influenza diagnoses. Less than half (49.6%, 398/802) of all RSV cases received RSV-specific ICD codes (such as J20.5: ‘acute bronchitis due to RSV’) (5). Considering these challenges, we were interested in the question whether point of care testing could help us make accurate diagnoses more quickly and also to make the test results known to the patients and their caretakers while they were still with us in the Emergency Department (ED) (6).…”
Section: Questions and Answersmentioning
confidence: 99%